Strategic delegation improves cartel stability - Martijn A. Han (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Fershtman and Judd (1987) and Sklivas (1987) show that strategic delegation reduces firm profits in the one-shot Cournot game. Allowing for infinitely repeated interaction, strategic delegation can increase firm profits as it improves cartel stability.
Keywords: D43; L13; L20; L41; 330; strategic delegation; collusion; cartel stability; Kartell; Gleichgewichtsstabilität; Wiederholte Spiele; Kooperative Führung; Theorie